Quality of Life in Women with Deep Endometriosis: A Cross-Sectional Study - Yela, Daniela Angerame; Quagliato, Iuri de Paula; Benetti-Pinto, Cristina Laguna (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To describe clinical and sociodemographic characteristics of women with deep infiltrating endometriosis (DIE) and assess their quality of life (QOL) during 6 months of medical treatment.Methods A descriptive cross-sectional study of 60 women diagnosed with DIE either by surgery or image methods (ultrasound or magnetic resonance), who received clinical treatment for at least 6 months in the Universidade de Campinas, Campinas, state of São Paulo, Brazil. Both the SF-36 and the EHP-30 questionnaires were used to assess the quality of life.Results The mean age of the patients was 37.7 ± 6.0 years old, with 50% presenting dysmenorrhea; 57% dyspareunia; and 50% chronic pelvic pain. The SF-36 and the EHP-30 revealed impaired quality of life. In the SF-36, the worst domains were limitation due to emotional aspects (40.2 ± 43.1) and self-esteem and disposition (46.1 ± 24.8), whereas in the EHP-30 they were social well-being (50.3 ± 30.6); infertility (48.0 ± 36.3); and sexual intercourse (54.0 ± 32.1).Conclusion Although clinically treated, women with deep endometriosis present impairment in different domains of quality of life regardless of the questionnaire used for evaluation.
Keywords: endometriosis; quality of life; pelvic pain; dysmenorrhea